Whole exome association of rare deletions in multiplex oral cleft families. Issue 1 (1st December 2016) - Fu, Jack; Beaty, Terri H.; Scott, Alan F.; Hetmanski, Jacqueline; Parker, Margaret M.; Wilson, Joan E. Bailey; Marazita, Mary L.; Mangold, Elisabeth; Albacha‐Hejazi, Hasan; Murray, Jeffrey C.; Bureau, Alexandre; Carey, Jacob; et al.
ABSTRACT: By sequencing the exomes of distantly related individuals in multiplex families, rare mutational and structural changes to coding DNA can be characterized and their relationship to disease risk can be assessed. Recently, several rare single nucleotide variants (SNVs) were associated with an increased risk of nonsyndromic oral cleft, highlighting the importance of rare sequence variants in oral clefts and illustrating the strength of family‐based study designs. However, the extent to which rare deletions in coding regions of the genome occur and contribute to risk of nonsyndromic clefts is not well understood. To identify putative structural variants underlying risk, we developed a pipeline for rare hemizygous deletions in families from whole exome sequencing and statistical inference based on rare variant sharing. Among 56 multiplex families with 115 individuals, we identified 53 regions with one or more rare hemizygous deletions. We found 45 of the 53 regions contained rare deletions occurring in only one family member. Members of the same family shared a rare deletion in only eight regions. We also devised a scalable global test for enrichment of shared rare deletions.